ANALYSIS OF THE EFFECTS OF FERTILIZER ON THE QUALITY OF THE MUSTARD PLANT (BRASSICA CHENENSIS L) USING REGRESSION LOGISTICS METHOD - Rufina Rahma Ajeng Setyaningsih; Hindriyanto Dwi Purnomo (Informatika, Universitas Jenderal Soedirman, 2022)
Based on the existing problems related to the trial of fertilizer produced by PT Petrokimia Gresik with the ZA variant on pakcoy plants with polybag, this study aimed to determine the best fertilizer for mustard pakcoy and the relationship between root length, plant height, number of leaves and plant weight due to ZA variation of fertilizer application. The research was carried out at the Greenhouse of the Research Department of PT Petrokimia Gresik in January 2022. This study was visualized between the variables and processed using the binary logistic regression method. The data obtained was then processed using three tools, namely Jupyter notebook, Power BI, and Rstudio. The results showed that the relationship between root length, body weight had a different relationship with treatment and the number of leaves that were not in the same direction with good treatment for mustard pakcoy with polybag media was behavior B, where B contained 2,000 kg of Petroganic fertilizer, 400 kg of NPK, Urea NPBPT (2) 300kg.